VELLALAS OF TAMIL NADU - Sasilekha.S.S,; Joel, Dr. T. Wins (International Journal of Psychosocial Rehabilitation, 2020)
Vellalar is a Tamil Caste found mainly in the Indian States of Tamil Nadu, Kerala and in North Eastern parts of Sri Lanka. They are traditionally involved in agriculture also serving as landlords. Vellalar, is a generic term used by several agricultural communities, including the numerically strong kongu Vellalar, Chozhia Vellalar, Thuluva Vellalar and Sri Lankan Vellalar. Despite being a relatively lowly group, they were dominant communities in Tamil Agrarian Societies for 600 years until the decline of the Chola Empire in the 13th Century